2012
DOI: 10.1038/emboj.2012.191
|View full text |Cite
|
Sign up to set email alerts
|

ATM/ATR checkpoint activation downregulates CDC25C to prevent mitotic entry with uncapped telomeres

Abstract: Shelterin component TRF2 prevents ATM activation, while POT1 represses ATR signalling at telomeres. Here, we investigate the mechanism of G2/M arrest triggered by telomeres uncapped through TRF2 or POT1 inhibition in human cells. We find that telomere damage-activated ATR and ATM phosphorylate p53, as well as CHK1 and CHK2, thus activating two independent pathways to prevent progression into mitosis with uncapped telomeres. Surprisingly, telomere damage targets the CDC25C phosphatase for proteasome degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 55 publications
2
62
0
Order By: Relevance
“…56 Uncapped telomeres activated the ATM/ATR-Chk1/Chk2 pathway and promoted Cdc25C degradation, preventing mitotic entry. 57 BRCA1 overexpression in p53 wild-type MCF-7 cells led to a G2 arrest that was accompanied by activation of ERK1/2 and a decrease in Cdc25C protein. Here, the BRCA1/BARD1 complex was identified as an E3 ligase for Cdc25C.…”
Section: Discussionmentioning
confidence: 92%
“…56 Uncapped telomeres activated the ATM/ATR-Chk1/Chk2 pathway and promoted Cdc25C degradation, preventing mitotic entry. 57 BRCA1 overexpression in p53 wild-type MCF-7 cells led to a G2 arrest that was accompanied by activation of ERK1/2 and a decrease in Cdc25C protein. Here, the BRCA1/BARD1 complex was identified as an E3 ligase for Cdc25C.…”
Section: Discussionmentioning
confidence: 92%
“…Chk1/Chk2-mediated phosphorylation of p53 results in up-regulation of p21, which functions as a Cdk2 inhibitor. This halts the cell cycle at G1-phase until damage is repaired and the ATM/ ATR-induced repression is lifted [98][99][100][101]. Activation of Cdk1 by cyclin B is required for the initiation and completion of mitosis and is the primary target via which the G2/M checkpoint can inhibit mitotic entry.…”
Section: Atm/atr Pathwaysmentioning
confidence: 98%
“…Cells with defective ATM or p53 escape from G 2 arrest and enter mitosis with persisting telomere dysfunction-induced foci on mitotic chromosomes (20). However, recent studies indicated that DDR is attenuated in mitosis compared with interphase (21)(22)(23), and thus cells may respond differently to telomere damage induced during mitosis (24).…”
mentioning
confidence: 99%
“…DNA lesions and uncapping of the telomere during interphase of the cell cycle both activate ATM and ATR kinases, phosphorylation of downstream kinases Chk1 and Chk2, and the transcription factor p53, which leads ultimately to cell cycle arrest with a persistent DDR (17)(18)(19). In vertebrate cells, uncapped telomeres induce G 2 arrest through the inactivation and degradation of cyclin B by activating the phosphatase Cdc25C (20) as well as the up-regulation of the Cdk inhibitor p21 (17). In addition to activation of DDR kinases, unprotected or damaged telomeres are also marked by phosphorylation of H2AX (␥-H2AX) and recruit a number of repair proteins, such as MDC1 and 53BP1, which form telomere dysfunction-induced foci (17,18).…”
mentioning
confidence: 99%